Concentrações plasmáticas e peritoneal da proteína de fase aguda HMGB1 em bezerros portadores ou não de hérnias umbilicais - Poló, Tatiane da Silva [UNESP] (2012)
HMGB1 protein may act by promoting an inflammatory response. Thus, the goals of this study were to quantify plasma and peritoneal fluid concentrations of HMGB1 in calves with or without congenital umbilical hernia before and after surgery, as well as assess their levels during serial paracentesis used as an auxiliary diagnostic tool for assessing the inflammatory response in the abdominal cavity. The presence of a congenital umbilical hernia caused increased values of HMGB1 in plasma and peritoneal fluid. The herniorraphy was not a stimulus intense enough to increase the concentration of this protein in the peripheral blood. However, in the peritoneal fluid, HMGB1 levels were increasead from 7 to 15 days after surgery, in response to the inflammatory process established in the abdominal cavity postoperatively. Serial paracentesis caused an increase of HMGB1 levels in the peritoneal fluid only, showing a mild inflammatory process, returning to baseline values after a longer interval between punctures. Thus, the presence of congenital umbilical hernias in calves cause local and systemic changes in HMGB1 levels both in plasma and in the peritoneal fluid while herniorraphy and serial paracentesis cause later changes in HMGB1 levels only in the peritoneal fluid